Pengaruh Lingkungan Kerja Terhadap Semangat dan Kegairahan Kerja Karyawan Pada Kantor Administrator Pelabuhan Makassar - Kamaruddin Kamaruddin (Jurnal Online Manajemen ELPEI, 2021)
The research aims to determine the effect of the work environment on employee morale and enthusiasm. The number of samples was taken as many as 60 people due to time and cost constraints. Meanwhile, the sampling technique used in this study was the Accidental Sampling method, in which the sample was selected by selecting anyone who was met at that time, in this case, the employee who was met at that time to answer the questionnaire. The data analysis tool used to test the hypotheses that have been proposed in this study is a qualitative descriptive method using a questionnaire. Based on the questionnaire distributed to the employee respondents at the Makassar Port Administrator's Office, it was shown that most of the respondents agreed or were satisfied that the work environment had a positive effect on employee morale and enthusiasm at the Makassar Port Administrator's Office. This can be seen from the answers of respondents who were very satisfied as much as 64.5%.